Relaxation mechanism of (x)Mn0.45Ni0.05Zn0.50Fe2O4 + (1 − x)BaZr0.52Ti0.48O3 multiferroic materials - Rahman, M Azizar; Hossain, A K M Akther (Physica scripta, 2014)
Polycrystalline (x)Mn0.45Ni0.05Zn0.50Fe2O4 + (1 − x)BaZr0.52Ti0.48O3 (with 0.2 ≤ x ≤ 0.8) multiferroic materials were prepared by the standard solid state reaction technique and samples prepared from these composites were sintered at 1200 °C. The impedance, electrical modulus, ac conductivity and dielectric permittivity were investigated over a wide range of frequencies (20 Hz-1 MHz) and at various temperatures (room temperature to 600 °C) to understand the relaxation phenomenon in these materials. X-ray diffraction patterns confirm the presence of a simple cubic spinel structure for the ferromagnetic phase and tetragonal peroveskite for the ferroelectric phase. Frequency-independent conductivity was observed in the low frequency region, which shifts to a higher frequency and dominates over a wide range of frequency (up to 1 MHZ) at higher temperature (600 °C). The transition temperature (∼675 °C) of these composites is higher than that of ferrite and ferroelectric phases. The frequency response electric modulus graphs for some composites show two maxima in the relaxation process. The first relaxation process appears at lower temperature and higher frequency with a lower value of activation energy for the composites containing more than 20% ferrimagnetic phase. This relaxation process is due to the first ionization energy of oxygen vacancies. The second relaxation process appears at all temperatures and at lower frequency, which shifts to higher frequency with increasing temperature, possessing a comparatively higher value of activation energy. This relaxation process is attributed to the Maxwell-Wagner-Sillars relaxation phenomenon. The frequency-dependent impedance and modulus plots exhibit a non-coincidence of relaxation peaks, indicating the deviation from the Debye-type relaxation process.